Diseño de una herramienta digital para la planificación de la producción y optimización de la capacidad instalada en el proceso de fabricación de productos alimenticios empacados al vacío. (2025)
This research study focuses on improving production planning and installed capacity in the food sector. It proposes the development of a digital tool that assists companies to quickly adjust to market changes and enhance their efficiency and competitiveness. A case study has been analyzed in a company of prepared and vacuum-packed foods located in the city of Bogotá. The main problem has been identified as the poor management of the supply chain that caused erroneous estimates in delivery dates and the presence of products not suitable for sale. These aspects generated a loss of confidence and stagnation in the growth of the organization. The lack of tools to predict production has resulted in operational inefficiencies and low quality of the final product, in addition to increased costs due to additional processes that have negatively affected its competitiveness in the market.